Implementasi Lean Hospital dalam Meningkatkan Pelayanan Rawat Jalan Poliklinik Penyakit dalam di RSUD Sabang - Ema Nurul Tafaqa; Chrismis Novalinda Ginting; Ali Napiah Nasution (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Effective outpatient care is an indicator of hospital service quality and must meet the Ministry of Health’s Minimum Service Standards (MSS), particularly the waiting time requirement of ≤ 60 minutes. However, many healthcare facilities have yet to meet this standard. This study aims to analyze the implementation of Lean Hospital practices in improving service efficiency and compliance with MSS at the Internal Medicine Outpatient Clinic of Sabang City Regional General Hospital. The study employed a quantitative cross-sectional design using observation, time-motion studies, and the SERVQUAL questionnaire, with Spearman and Pearson correlation analyses. Findings revealed an average service time of 87 minutes, exceeding MSS (≤ 60 minutes), with non–value-added activities accounting for 55 minutes and waiting waste at 40%. The Process Cycle Efficiency (PCE) value of 36.7% indicates low efficiency. Patient satisfaction was high (mean 3.43), but higher among those meeting MSS (43.4%) compared to those exceeding it (6.7%). There was a significant relationship between waiting time and satisfaction (r = −0.612; p < 0.05), and between Lean implementation and process efficiency (r = 0.683; p < 0.05). Conclusion: Failure to meet MSS is associated with low efficiency and suboptimal Lean implementation. Improvements should focus on eliminating waiting waste and strengthening kaizen to enhance service quality and patient satisfaction